2017
DOI: 10.1515/ijamh-2016-0116
|View full text |Cite
|
Sign up to set email alerts
|

Work related musculoskeletal disorders among adolescent girls and young women employees of textile industries in Tamil Nadu, India – a comparative study

Abstract: Musculoskeletal disorders are common in those employed in the textile industry. The aim of the study is to assess musculoskeletal disorders among adolescent girls who are current employees of textile industries in comparison with the adolescent girls and young women who are past employees of textile industries and adolescent girls who have never been employed in the textile industry. Methodology This is a cross-sectional study. A total of 321 subjects, 107 in each study group were sampled. Standardized nordic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…ese studies reported the following prevalence rates: 79% in the manufacturing industry in Brazil [9], 41.5% among Iranian petrochemical industries [10], and 97.3% among textile industry workers in India [11].…”
Section: Introductionmentioning
confidence: 99%
“…ese studies reported the following prevalence rates: 79% in the manufacturing industry in Brazil [9], 41.5% among Iranian petrochemical industries [10], and 97.3% among textile industry workers in India [11].…”
Section: Introductionmentioning
confidence: 99%